Critical and Creative Thinking education in Higher Education Institutions (Revista Lusófona de Educação, 2019)
Stéphan Vincent-Lancrin, from the Center for Educational Research and Innovation of the Organisation for Economic Co-operation and Development (OECD-CERI), talks with Caroline Dominguez, coordinator of the ‘Critical Thinking Across the European Higher Education Curricula – CRITHINKEDU’ European project, about Critical and Creative Thinking education in Higher Education Institutions.